»Kto znał – niech wspomni«. O prywatnych nekrologach w czeskiej, słowackiej i polskiej prasie - Olchowa, Gabriela (Komisja Slawistyczna PAN, Oddział w Poznaniu, IFS UAM, Wydawnictwo PRO, 2018)
The subject of interest was made obituaries on the anniversary of the deceased’s death announced by his relatives. The aim was to determine the structure of this funeral genre, describe the linguistic means used and provide typical features. Differences and similarities were indicated on the basis of comparative studies. The analysis included private anniversary obituaries included in the Czech, Slovak and Polish local press, which were published from 01/08/2017 to 31/12/2017. Solid components were created forming the structure of the studied texts: date of death anniversary; identification data of the deceased; memory; signature of the sender. The most distinguished are Polish obituaries, because they are the only ones that are not only a memory of a loved one’s death, but above all they announce a holy mass for the deceased or invite for a common prayer, which is confirmed by the deeply rooted tradition and influence of Christianity on Polish culture. On the other hand, Czech and Slovak obituaries have the most common features, which, apart from minor differences, are identical. It was found that the texts studied have a stereotypical construction, often reproduced diagrams and a formulic language shape. The isolated and the most important part is devoted to the deceased, who is shown from the point of view of the mourners and the feelings they have, while the final formulas differentiate the obituaries within the studied languages. Studies have confirmed that the expression of remembrance of the deceased on the anniversary of his death is a customary behavior in Western Slavic cultures.
»Who knew – mention«. About private obituaries in the Czech, Slovak and Polish press
Keywords: obituary; funeral genres; Czech language; Polish language; Slovak language